Talking War: Representation, Veterans and Ideology in Post-War Parliamentary Debates. Issue 1 (10th January 2022) - Mochtak, Michal; Glaurdić, Josip; Lesschaeve, Christophe
Abstract: How do politicians in post-war societies talk about the past war? How do they discursively represent vulnerable social groups created by the conflict? Does the nature of this representation depend on the politicians' ideology or their record of combat service? We answer these questions by pairing natural language processing tools and a large corpus of parliamentary debates with an extensive data set of biographical information including detailed records of war service for all members of parliament during two recent terms in Croatia. We demonstrate not only that veteran politicians talk about war differently from their non-veteran counterparts, but also that the sentiment of war-related political discourse is highly dependent on the speaker's exposure to combat and ideological orientation. These results improve our understanding of the representational role played by combat veterans, as well as of the link between descriptive and substantive representation of vulnerable groups in post-war societies.